Pengaruh Gaya Hidup Dan Lokasi Terhadap Minat Beli Coffe Shop Kopi Kita Cabang Jati Padang - Muhammad Ridho; Puti Embun Sari (GLOBAL SCIENTS PUBLISHER, 2025)
This study analyzes the influence of lifestyle on consumer purchasing decisions in fashion thrifting, with purchase intention as an intervening variable using a quantitative method. The research aims to determine the effect of lifestyle on consumer purchasing decisions in fashion thrifting, with purchase intention as an intervening variable. This study employs a survey method with a quantitative approach, where data was collected from 96 respondents who are thrifting consumers. The population in this study consists of all consumers who purchase fashion thrifting in Padang City, with an unknown exact number, and the research sample was selected using purposive sampling. Data collection was conducted through questionnaires distributed to all respondents, which were then analyzed using SEM-PLS (Structural Equation Modeling – Least Square). The results show that lifestyle has a direct and significant effect on purchasing decisions, although this effect becomes stronger when mediated by purchase intention. The intervening variable test indicates that purchase intention strengthens the relationship between lifestyle and purchasing decisions. Thus, purchase intention serves as a significant intervening variable in this study.